The Influence of Green Innovation, Corporate Social Responsibility, and the Work Environment in Increasing Competitiveness - Justin Sarmili, Marvellius; Widhia Rahayu, Ni Putu (Lafadz Jaya Publisher, 2024)
The number of Tunas Honda branches in Bandar Lampung, initially 8, has decreased due to intensified competition. This research was conducted to examine how green innovation, corporate social responsibility, and the work environment influence competitiveness at Tunas Honda in Bandar Lampung. Employing a quantitative approach, data were gathered via an online questionnaire employing a Likert scale, with a population of 40 individuals selected through purposive sampling, representing the entire population. Analysis was conducted using multiple linear regression tests aided by SPSS version 20, alongside hypothesis tests such as the t-test and F-test. The results indicate that green innovation, corporate social responsibility, and the work environment significantly and positively impact competitiveness.